Legal Analysis of the Fostering and Supervision of Village Based on the Village Law 2014 - Syamsuddin, Adiesty S.P.; Korompot, Ratu Ratna; Jubair , Jubair; Baco, Syamsuddin; Miqat, Nurul (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2022)
The position of the village as the lowest autonomous government structure has an essential role in achieving multidimensional national development goals because its management involves all government officials, both at the main and the local level, even at the village level. This study aimed to determine the material normative regulation related to the supervision and guidance of the administration of village governance and to find out the substantive forms of supervision and direction of the administration of village governance that the level of government above can implement. The result of this study was 1) Normative regulation material on the supervision and development of village administration is currently subject to Law Number 6 of 2014 concerning Village Government Regulation of the Republic of Indonesia Number 47 of 2015 concerning Amendment to Government Regulation Number 43 of 2014 concerning Implementation Regulation of Law Number 6 of 2014 concerning Villages, and PP Number 12 of 2017. 2) Substantive forms of supervision and development of village administration that can be carried out by the government level above include the provision of technical guidelines/guidance, appreciation, and guidance in the fields of development planning, finance, and institutional planning.